Peningkatan Pembelajaran Matematika dengan Model Pembelajaran POE (Predict-Observe-Explain) pada Siswa - Bhoes, Nadya Permata Putri; Nurasharaeni Mardania D (JKPD (Jurnal Kajian Pendidikan Dasar), 2025)
The teaching-learning process requires effective classroom management skills, as each student has different abilities and ways of thinking. Teachers are expected to select the appropriate approach and teaching model to ensure that students can better understand the subject matter. This study aims to analyze the application of the Predict-Observe-Explain (POE) learning model in improving mathematics learning outcomes for second and third grade students at UPTD SPF SDN 21 Barru. Through Classroom Action Research (CAR), this study evaluates the impact of the POE model on students' learning outcomes in two cycles. In the pre-cycle, the average score of students was 51.27, which then increased to 54.81 in the first cycle and 73.14 in the second cycle, showing significant improvement and reaching the expected standard. The POE steps, which include prediction, observation, and explanation, encourage students to think critically, actively participate, and understand the material more deeply. Furthermore, this model helps teachers create more interactive and engaging lessons through creative classroom management. The results of this study demonstrate that the POE model not only improves student learning outcomes but also provides a more meaningful and effective learning experience. Therefore, POE has proven to be an effective teaching model in mathematics learning, supporting material mastery and enhancing student motivation.